Produksi Gas Metana (CH4) dari Feses Sapi FH Laktasi dengan Pakan Rumput Gajah dan Jerami Padi - Puspitasari, R.; Muladno, Muladno; Atabany, A.; Salundik, Salundik (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
The aim of this experiment  was to compare the production of methane gas from lactating dairy cow feces by feeding with elephant grass (EG) and rice straw (RS). BALINGTAN methode in measuring methane gas was used in this research. Feces were collected as much as 1 kg in 24 hours and incubated for 8 weeks to measure methan gas. CRD (Complete Random Design) repeated measurements was used with 3 treatments : RS (100% rice straw), EG (100% elephant grass) and RSEG (50% rice straw + 50% elephant grass). Measured variables were methane gas, proximate feed analysis, feces proximate analysis, total of feces organic matter, ADF and NDF feces, C organics feces. Based on the research results generated methane gas production from lactating dairy cow feces had no significant in each treatment (P>0.05). The incubation process for 8 weeks showed a decreased of feces’s substrate and organic matters, significantly.  The decline of feces’s organic matter during fermentation was followed by methane gas production on 8th week in all treatments. It can be concluded that methane gas production from lactating dairy cow feces from RS, EG and RSEG produces methane equals but potentially, RS and RSEG higher than EGKeywords : methane gas, feces, lactating dairy cows, elephant grass, rice straw